2015
DOI: 10.1111/jce.12705
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of Subcutaneous Implantable Cardioverter Defibrillator Implantation in Patients with End‐Stage Renal Disease on Dialysis

Abstract: Our data suggest that S-ICD implantation in dialysis patients is not associated with an excess risk of implant related complications or inappropriate shocks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
29
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(32 citation statements)
references
References 20 publications
3
29
0
Order By: Relevance
“…This result was later confirmed in other studies 90. The incidence of appropriate shocks delivered by S‐ICD was significantly higher in the dialysis cohort compared with the nondialysis group, with a low risk of inappropriate shocks 87. Given the high prevalence of CHF in the dialysis population, S‐ICD appears to be an appropriate alternative to transvenous ICD for primary and secondary prevention.…”
Section: Chf In Patients With Esrdsupporting
confidence: 68%
See 2 more Smart Citations
“…This result was later confirmed in other studies 90. The incidence of appropriate shocks delivered by S‐ICD was significantly higher in the dialysis cohort compared with the nondialysis group, with a low risk of inappropriate shocks 87. Given the high prevalence of CHF in the dialysis population, S‐ICD appears to be an appropriate alternative to transvenous ICD for primary and secondary prevention.…”
Section: Chf In Patients With Esrdsupporting
confidence: 68%
“…Patients with advanced CKD and ESRD tend to have higher rates of acute and chronic complications from device placement and higher mortality unrelated to cardiac arrhythmias 86. A study of a cohort of >9500 patients on chronic dialysis implanted with ICDs revealed that 11% of patients died of an infection at 1.4 years of follow‐up, with most infections occurring 1 year after device implantation 87. The incidence of device infection in patients with ESRD is 2 to 5 times greater than in patients without ESRD,88, 89 and this may be the result of frequent bloodstream access for hemodialysis 88, 89.…”
Section: Chf In Patients With Esrdmentioning
confidence: 99%
See 1 more Smart Citation
“…57 In the dialysis population, TV leads pose a risk of central venous stenosis which, in the setting of arteriovenous access in an ipsilateral upper extremity, can lead to considerable significant upper extremity and facial edema. In fact, the prevalence of central vein occlusion in patients with chronic defibrillator leads is a high as seven percent.…”
Section: A C C E P T E Dmentioning
confidence: 99%
“…In addition, it highlights some of the reasons why S-ICDs are of particular value in the hemodialysis patient population. Evidence is accumulating for the safety and efficacy of S-ICDs in patients with renal failure who are undergoing hemodialysis, but more is still needed 10, 11…”
Section: Resultsmentioning
confidence: 99%